Sensing and memorising liquids with polarity-interactive ferroelectric sound - Jong Sung Kim (Nature Portfolio, 2019)
Though liquid sensing platforms are highly sought after for emerging biomedical applications, current technology is limited in its capacity to directly sense and store information. Here, the authors report a sensing memory platform that senses, monitors, and stores information on various liquids.